Persepsi Ibu Nifas terhadap Pelayanan Kunjungan Nifas - Dyah Permata Sari (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2019)
The covered of porturition service supposed to more than or minimal same with chilbirth by the health staff. Because midewife more active doing the porturition call notiwithstanding to toward woman the chilbirth that helping by indigenous medical practitioner. But a matter of fact that happen about the problem of porturition call that is occur a drop out between the women and Health staf. Because that problem that research done to explaint the perception by women of porturion about porturition call service. The kind of this Research are the descriptif research with quantitative phenomenological. Variabel that researched are perception by women of porturion about porturition call serve. The Population of this Research are all of the women chilbirth in the Puskesmas Sooko Kecamatan Sooko Kabupaten Mojokerto that amount to 20 people. The technical that used is total sampling. This Research did in September 11th – December 4th, 2018. The instrument that used to roundup the file is the kuesioner and the did the processed file that include editing, coding, scoring, tabulating. The result of the Research is almost of the respondent have a positive perception by porturition serve. The observation by age, Education degree, and total of the child, have gotten more of the responden attain the age of 20-35 years old as much as 12 of the respondent (60%). Well educated of the responden are SMP as much as 15 of the respondent (75%), and including by total of the child as much as 14 of the responden have 2 child or for about 70%. Perception is the one of the indicator to explaint how much reaction of responden by the object that Raise in the Research. Result of the Research have indicated that women chilbirth have a positive perception about porturition call service. To advance the orturition call service might as well doing the elaboration intitutionaly